Preventive and therapeutic effects of physical exercise on bleomycin-induced lung injury and oxidative stress - Ricardo Aurino Pinho; Fernanda Schuveitzer Soares; Luís Gustavo Rocha; Cleber Aurino Pinho; Luciano Acordi da Silva las Acordi; Paulo César Look da Silveira (Universidade Federal de Santa Catarina, 2009)
Studies have shown that regular physical exercise of moderate intensity is an important tool for the control of pulmonary oxidative stress. The objective of this study was to examine the preventive and therapeutic effect of physical exercise on oxidative stress in the lungs of mice exposed to bleomycin (BLM). Thirty-six male mice (CF1, 30-35 g) received a single endotracheal dose of BLM (2.5 U/kg body weight dissolved in 0.25 mL 0.9% NaCl) or saline (0.9% NaCl) and were divided into six groups (n=6): untrained saline or BLM, preventive training saline or BLM, and therapeutic training saline or BLM. The trained groups underwent a program of progressive exercise on a treadmill for 8 weeks (up to 17 m.min-1, 50 min.day-1). The preventive group started the exercise program 62 days before the administration of BLM and the therapeutic group 62 days after the administration of BLM. All animals were killed by decapitation 48 hours after the experimental period, and the right lung was surgically removed for the determination of biochemical parameters. Hydroxyproline content, TBARS level, protein carbonylation, and superoxide dismutase (SOD) and catalase (CAT) activities were analyzed. The results showed that preventive and therapeutic training led to a significant reduction in hydroxyproline content and inhibited the increase in oxidative damage to lipids and proteins. However, only therapeutic training decreased SOD and CAT activities in mice exposed to BLM. The results suggest that preventive and therapeutic physical exercise is able to minimize pulmonary oxidative stress induced by BLM.